Conserved Transcription Factors Steer Growth-Related Genomic Programs in Daphnia. (14th July 2017) - Spanier, Katina I.; Jansen, Mieke; Decaestecker, Ellen; Hulselmans, Gert; Becker, Dörthe; Colbourne, John K.; Orsini, Luisa; De Meester, Luc; Aerts, Stein
Abstract: Ecological genomics aims to understand the functional association between environmental gradients and the genes underlying adaptive traits. Many genes that are identified by genome-wide screening in ecologically relevant species lack functional annotations. Although gene functions can be inferred from sequence homology, such approaches have limited power. Here, we introduce ecological regulatory genomics by presenting an ontology-free gene prioritization method. Specifically, our method combines transcriptome profiling with high-throughput cis -regulatory sequence analysis in the water fleas Daphnia pulex and Daphnia magna . It screens coexpressed genes for overrepresented DNA motifs that serve as transcription factor binding sites, thereby providing insight into conserved transcription factors and gene regulatory networks shaping the expression profile. We first validated our method, called Daphnia-cis Target, on a D. pulex heat shock data set, which revealed a network driven by the heat shock factor. Next, we performed RNA-Seq in D. magna exposed to the cyanobacterium Microcystis aeruginosa. Daphnia-cis Target identified coregulated gene networks that associate with the moulting cycle and potentially regulate life history changes in growth rate and age at maturity. These networks are predicted to be regulated by evolutionary conserved transcription factors such as the homologues of Drosophila Shavenbaby and Grainyhead, nuclear receptors, and a GATA family member. In conclusion, our approach allows prioritising candidate genes in Daphnia without bias towards prior knowledge about functional gene annotation and represents an important step towards exploring the molecular mechanisms of ecological responses in organisms with poorly annotated genomes.